Children's rights and the developing law - Fortin, Jane (LexisNexis, 2003)
Provoked by the implementation of the Human Rights Act 1998, interest in the concept of children's rights has grown significantly since the first edition of this work was published. Now in its second edition, Children's Rights and the Developing Law explores the way developing law and policy in England and Wales are simultaneously promoting and undermining the rights of children. It reflects on the extent to which these developments take acco unt of children's interests, using a range of current research on children's needs as a template against which to assess their value. A critical approach is maintained throughout the work, particularly when assessing the extent to which the concept of children's rights is being developed by the domestic courts and the degree to which the UK is complying with its obligations to implement the UN Convention on the Rights of the Child. Wide reaching in its scope, the work starts with the theoretical perspectives of the concept of children's rights and the extent to which international activity in the field of human rights can be utilised to inform domestic law.